Modeling & Simulation of electromagnetic phenomena in anisotropic mediums (Damascus University Journal for engineering sciences, 2023)
This paper deals with the modeling of electromagnetic interactions in the anisotropic medium and its comparison with Isotropic medium. Anisotropic media characterized with electrical properties which are varied in the spatial dimensions, depending on the direction compared to isotropic media which are direction independent. Various phenomena occur in these media such as propagation, scattering, reflections and multiple refractions. These constitutes complex view of connected phenomenon with this interaction, which is reflected in Maxwell's equations and their solutions. Computational electromagnetics, including the Finite Difference Time Domain (FDTD) method, play a key role in modeling and simulation for analyzing these phenomena. Anisotropic properties add difficulties to the interaction of these media with electromagnetic waves. The study required a modification of the approximate solutions of Maxwell's equations, and the formation of the appropriate solution grid for anisotropic properties of FDTD method.The results of the research produce an atypical interactions of electromagnetic waves, and it gives the possibility to follow the anisotropic electromagnetic wave interaction, wave multiple reflections, scattering, the speed variation of the components, its polarization and its spatial pattern. These results could be applied in some engineering applications e.g. EM shielding, analysis of dielectric materials structures and etc.
Keywords: Anisotropic materials; Isotropic materials; electromagnetic Fields; Finite Difference Time Domain FDTD; CST software; Polarization